Behavior of skin temperature during incremental cycling and running indoor exercises - Tatiane Lie Igarashi; Tiago Lazzaretti Fernandes; Arnaldo José Hernandez; Carlos Eduardo Keutenedjian Mady; Cyro Albuquerque (Heliyon, 2022)
The study of the human body's energy behavior has received more attention over the past years. The development of thermal infrared cameras brought new possibilities for evaluating physical exercise performance. This work aims to study the skin temperature distribution during treadmill running and cycle ergometer tests with a graded load exercise until exhaustion. Eight amateur athletes performed both tests. In addition, the ventilatory and metabolic data were measured by indirect calorimetry. The thermoregulatory system is highly requested to maintain the internal body temperature. Consequently, the average skin temperature decreased during running and cycling tests, although with a higher variation in running. It was observed that the lower limbs had a similar performance for both exercises; on the other hand, the upper limbs had a higher temperature decrease for running. This may be explained by increased body energy transfer to the environment due to higher degrees of freedom during the test. The main contribution is comparing the thermal behavior of the person's skin performing two different activities, constructing a basis for future energy and exergy analysis of the human body under physical activities complementary to the literature.